The deletion of AQP4 and TRPV4 affects astrocyte swelling/volume recovery in response to ischemia-mimicking pathologies - Hermanova, Zuzana; Valihrach, Lukas; Kriska, Jan; Maheta, Mansi; Tureckova, Jana; Kubista, Mikael; Anderova, Miroslava (Frontiers in Cellular Neuroscience, 2024)
Astrocytic Transient receptor potential vanilloid 4 (TRPV4) channels, together with Aquaporin 4 (AQP4), are suspected to be the key players in cellular volume regulation, and therefore may affect the development and severity of cerebral edema during ischemia. In this study, we examined astrocytic swelling/volume regulation recovery in mice with TRPV4 and/or AQP4 deletion in response to in vitro ischemic conditions, to determine how the deletion of these channels can affect the development of cerebral edema. We used three models of ischemia-related pathological conditions: hypoosmotic stress, hyperkalemia, and oxygen-glucose deprivation (OGD), and observed their effect on astrocyte volume changes in acute brain slices of Aqp4 -/-, Trpv4 -/-and double knockouts. In addition, we employed single-cell RT-qPCR to assess the effect of TRPV4 and AQP4 deletion on the expression of other ion channels and transporters involved in the homeostatic functioning of astrocytes. Quantification of astrocyte volume changes during OGD revealed that the deletion of AQP4 reduces astrocyte swelling, while simultaneous deletion of both AQP4 and TRPV4 leads to a disruption of astrocyte volume recovery during the subsequent washout. Of note, astrocyte exposure to hypoosmotic stress or hyperkalemia revealed no differences in astrocyte swelling in the absence of AQP4, TRPV4, or both channels. Moreover, under ischemia-mimicking conditions, we identified two distinct subpopulations of astrocytes with low and high volumetric responses (LRA and HRA), and their analyses revealed that mainly HRA are affected by the deletion of AQP4, TRPV4, or both channels. Furthermore, gene expression analysis revealed reduced expression of the ion transporters KCC1 and ClC2 as well as the receptors GABAB and NMDA in Trpv4 -/-mice. The deletion of AQP4 instead caused reduced expression of the serine/cysteine peptidase inhibitor SERPINa3n. Thus, we also showed that in AQP4 or TRPV4 knockouts, not only the specific function of these channels is affected, but also the expression of other proteins, which may modulate the ischemic cascade and thus influence the final impact of ischemia.